2022
DOI: 10.21203/rs.3.rs-1783762/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Review on the strategies for enhancing mechanical properties of bacterial cellulose

Abstract: Bacterial cellulose (BC) is a pure biopolymer with abundant sources. BC has been used in wound dressings, artificial blood vessels, bone tissue engineering, and other applications because of its microporosity, excellent water retention, thermal stability, and biocompatibility. Despite this, the mechanical qualities of dehydrated BC are poor, and its strength and toughness are insufficient for the application. The mechanical properties of BC are influenced by the three-dimensional (3D) nano-network structure, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Elongation at break, also known as ductility, is the material's capacity to deform under stress determined by calculating the area underneath the stress-strain curve of bacterial cellulose. 57 The mechanical strength evaluation is depicted in Figure 8. The study demonstrated that BC210 had the highest tensile strength and elongation at break, at © 2024 the authors.…”
Section: Figure 3: Weight Evaluation Of Bacterial Cellulosementioning
confidence: 99%
“…Elongation at break, also known as ductility, is the material's capacity to deform under stress determined by calculating the area underneath the stress-strain curve of bacterial cellulose. 57 The mechanical strength evaluation is depicted in Figure 8. The study demonstrated that BC210 had the highest tensile strength and elongation at break, at © 2024 the authors.…”
Section: Figure 3: Weight Evaluation Of Bacterial Cellulosementioning
confidence: 99%